2021
DOI: 10.1136/medethics-2020-107071
|View full text |Cite
|
Sign up to set email alerts
|

Should age matter in COVID-19 triage? A deliberative study

Abstract: The COVID-19 pandemic put a large burden on many healthcare systems, causing fears about resource scarcity and triage. Several COVID-19 guidelines included age as an explicit factor and practices of both triage and ‘anticipatory triage’ likely limited access to hospital care for elderly patients, especially those in care homes. To ensure the legitimacy of triage guidelines, which affect the public, it is important to engage the public’s moral intuitions. Our study aimed to explore general public views in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 15 publications
2
56
0
1
Order By: Relevance
“… Emanuel et al, 2020 ; Farrell et al, 2020 ). Our finding that members of the Swiss public would not base triage decisions on the patient's age, in combination with similar results from other countries ( Kuylen et al, 2021 ), lends support to voices that suggest caution in using age as a criterion ( Farrell et al, 2020 ). Our findings also suggest that there might be a discrepancy between Swiss public sentiment and the existing Swiss guidelines ( Scheidegger et al, 2020 ), according to which age is considered under some conditions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“… Emanuel et al, 2020 ; Farrell et al, 2020 ). Our finding that members of the Swiss public would not base triage decisions on the patient's age, in combination with similar results from other countries ( Kuylen et al, 2021 ), lends support to voices that suggest caution in using age as a criterion ( Farrell et al, 2020 ). Our findings also suggest that there might be a discrepancy between Swiss public sentiment and the existing Swiss guidelines ( Scheidegger et al, 2020 ), according to which age is considered under some conditions.…”
Section: Discussionsupporting
confidence: 76%
“…However, several related studies from other countries have produced similar results. In the UK, Kuylen et al (2021) found, as mentioned above, that the public is reluctant to use age as a criterion for pandemic triage. In addition, Larsen and Schaeffer (2020) found similar to us a pronounced tendency to discriminate against foreigners in the allocation of medical care in Denmark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, services will need to weigh up various ethical positions to decide how important age is to these admission policies. 11 It is therefore important that older persons’ subjective outcomes are better understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is the astonishing fact that such triage has to be used owing to COVID-19 infection. 15 In other words, it showed the impact of overturning the medical ethics that underlie geriatrics and rehabilitation medicine.…”
mentioning
confidence: 99%